Canine Brucellosis: Insights Into the Epidemiologic Situation in Europe - Buhmann, Gesine; Paul, Frauke; Herbst, Werner; Melzer, Falk; Wolf, Georg; Hartmann, Katrin; Fischer, Andrea (Frontiers in Veterinary Science, 2019)
Discospondylitis is a frequent cause of spinal pain in veterinary neurology and requires long-term antibiotic treatment. Brucella canis is one of many responsible pathogens of discospondylitis in dogs and requires specific management. There is a lack of data on the current epidemiologic situation of canine brucellosis in Europe. The purpose of the study was to report recent cases of Brucella canis discospondylitis in Germany and to investigate the laboratory frequency and geographic origin of Brucella canis-positive samples in Europe. A medical records search in the neurology service identified dogs with a diagnosis of discospondylitis due to Brucella canis infection. The database of a European veterinary diagnostic laboratory was screened for Brucella spp. PCR- or Brucella canis antibody-positive samples. Brucella canis infection was diagnosed in four young dogs with discospondylitis, which had been imported to Germany from Eastern European countries (Moldova, Romania, Macedonia). Treatment with doxycycline and pradofloxacin improved the clinical signs in all four dogs and long-term resolution of clinical signs was observed in two dogs. In the European veterinary diagnostic laboratory, 3.7% of submitted samples (61/1657) were PCR-positive and 5.4% of submitted samples (150/2764) tested positive for Brucella canis antibodies. Brucella spp. PCR-positive samples originated from Spain (11.1% of submitted samples), Poland (6.7% of submitted samples) and rarely from Italy and France. Samples with Brucella canis antibodies originated from 13 European countries (Sweden, Belgium, Austria, Switzerland, Italy, Finland, Germany, Denmark, Hungary, Norway, Poland, France, Netherlands). In conclusion, infection with Brucella canis needs to be considered in young dogs with discospondylitis in Europe and routine surveillance for Brucella canis infection appears indicated in dogs with a travelling history and spinal pain.